اسلامی مالیاتی نظام میں تسعیر کے اصول و ضوابط: فقہی تناطر میں تحقیقی مطالعہ: Principles and guidelines of accounting in Islamic financial system: A research study in jurisprudential coherence - Dr Hafiz Zahid Farooq; Dr. Syed Hamid Farooq Bukhari (International Research Journal of Arabic and Islamic Studies, 2024)
Or this, after God Almighty, is the glory of Islamic jurisprudence, and the value of this ruling is a topic for you, Tawfiq Bakhshi. What are the results of this technique? The government of every party that sells coffee is reasonable. The price of our country's "pricing" is reasonable. The decision of your credit card is the right of the government, so that you can avoid it. It is permissible for the king to use the laws of the country. It is necessary. This company has a computer/delivery cadence, a computer that is connected to a computer compatible with the company on the other side. The price of the text is determined as a copy of the contract, which is identical to the company. A picture of the price is given at the specified price. An increase in the size of a picture of a forbidden benefit. First: The value of the Sultan's atmosphere, the two deputies of the bazaar and the law, the rule of the day, and the son of Saman Farrukht, he did not like it. Always: The price of this is unfair or forbidden, or it is permissible to use a logo that is not fair or that it is illegal. When the crumbs are broken, it is necessary to feel comfortable and reassured. This is an algebraic word that specifies a comprehensive fairness policy. This is forbidden. It is forced to return. What is the value of the atmosphere and interest or rent of a house? The opposite of the rent is obligatory. It is an obligation. Feel your cheek and prevent it For convenience: There is previous research on the topic, the most common thing is that the meaning is equal to the meaning of the meaning of the result, so that it is silent and that it is not without reason. It is appropriate to determine the value of the specified value, or else it will be different from that. The meaning is that it has come to you, meaning it is forbidden.